Urban–rural differences in primary school resources in China: a case study of Yuncheng County - Sun, Wenwen; Hu, Xin; Kidd, Akari Nakai; Li, Zhuoran; Liu, Chunlu (International Journal of Strategic Property Management, 2023)
Resources in primary schools can be classified into three types: campus, teaching, and community resources. Urban–rural differences in the resources of Chinese county schools, which are triggered by population migration and residents’ preference for high-quality schools, are a common phenomenon emerging in the context of rapid urbanization. Despite the negative effects of these resource differences on social sustainability and the increasing need to comprehensively analyze urban–rural differences in school resources, to date there has not been an effective analytical framework for resolving these issues. To address this research gap, this study develops a method using the entropy-based Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), spatial analysis, and statistical analysis for assessing resource equity in primary schools by means of the relative proximities of resources. The resource differences between urban and rural primary schools are quantitatively investigated through taking Yuncheng County as a case study. The urban–rural differences in the three types of resources are discovered and presented according to geographical location. The research findings make contributions to understanding the unbalanced distribution of school resources, promoting equity in education, and improving the social sustainability of counties. Additionally, the analytical framework has the potential to be extended to analyzing urban–rural resource differences in secondary or high schools.